Use of the Ball-Cratering Method to Assess the Wear Resistance of a Welded Joint of XAR400 Steel - Ligier, Krzysztof; Bramowicz, Mirosław; Kulesza, Sławomir; Lemecha, Magdalena; Pszczółkowski, Bartosz (Materials, 2023)
Wear-resistant steels are designed to allow for operation under extreme loading conditions. They combine large strength with resilience and resistance to abrasive wear. In stock, the steel is subjected to preliminary heat treatment. However, any further processing at temperatures higher than 200 °C results in tempering that influences the mechanical properties of the material. The presented paper aims to study changes in abrasive wear properties across the welded joint made out of this steel, and its prime novelty lies in using the ball-cratering method to test the wear resistance of the joints. To distinguish between different crystalline structures in the weld, metallographic and XRD analyses were performed that resulted in the determination of five primary zones for which wear tests were carried out. Abrasive wear rates, studied across the welded joint, indicate that the material in the HAZ has the lowest resistance to abrasive wear. Similarly, the obtained values of the wear index show decreasing resistance of the material approaching the joint axis.